Identification of a set of key aspects for heritage assets investments to support private operators in the decision-making processes - Di Liddo, Felicia; Locurcio, Marco; Morano, Pierluigi; Tatulli, Laura (Frontiers in Built Environment, 2025)
Heritage assets constitute a fundamental resource within territorial development strategies for their architectural, historical, and artistic value, serving as key drivers of sustainable and resilient planning. Their relevance in current urban governance stems from the wide range of interventions that involves this type of assets, such as adaptive reuse, which allow to obtain resource efficiency implementation, waste reduction and support the realization of projects that are more adaptable. These approaches not only contribute safeguard cultural identity but also create new revenues, strengthening the financial self-sufficiency of heritage sites. Considering the growing interest in these financial tool’s mechanisms, there is a clear need to better understand the investment dynamics associated with these assets. In response to this requirement, the present article conducts a systematic analysis of academic literature on the topic, following consolidated methodology, with the aim of collecting and organizing a set of components representative of the most critical aspects related to interventions on the built heritage. The resulting factor abacus is intended as a decision-support tool for financial developers, enabling more informed and strategic choices through a clearer understanding of key components. Based on a review of 30 academic contributions, the study identifies 14 factors grouped into 5 categories to highlight both their relative significance and their primary areas of influence. Additionally, the analysis distinguishes between discouraging and incentive factors, offering immediate insight into the risks and opportunities associated with a project and thereby supporting the private actors involved.